Performance Comparison of Integrated Modified Differential Phase Shift Keying (MD-DQPSK) and DQPSK in Dim Integrated OCDMA System - Gurpreet Kaur, Simarpreet Kaur, Simranjit Singh (International Journal of Advanced Science and Technology, 2019)
With the explosive increase in the online gaming, online video conferencing, HD television, pressure on optical communication is rapidly growing. Optical code division multiplexing caters user requirements because it can serve all users at the same time.Effect of modulation on the performance of OCDMA systems is prominent and phase shifting can bring better performance. Therefore, in proposed work, an emphasis is given to design an integrated modulation by combining features of two different modulations in newly demonstrated diagonal identity matrix based OCDMA system. A laser employed seven user spectral amplitude coded system is demonstrated at speed of 20 Gbps over 50 km SMF-28 link length and a comparison has been performed between MD-DQPSK and DQPSK modulation in terms of Q factor, BER and received power. It is perceived that MD-DQPSK is better than DQPSK due more pulse broadening tolerance. Keywords: Diagonal Identity Matrix (DIM), Modified differential phase shift keying (MD-DQPSK)Zero Cross correlation (ZCC)